Navigating Podcasts in the English Listening Classroom: A Library Research - Erniwati, Erniwati; Taqwim, Ahsani; Dewi, Anjar Kusuma; Arid, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
Podcasts, which consist of digital audio files, gains immense popularity as a technical resource for language acquisition, particularly among English language learners. The podcasts are attractive due to their flexibility, enabling learners to access language learning resources anytime and anywhere. This study was a-library research, comprising two categories of data. The primary data was sourced from a book entitled “Academic Podcasting and Mobile Assisted Language Learning